Development of Automated Attendance System Using Face Recognition - Pragathi, K.; Spandana, A.; Kumar, Ch. Santosh (Current Overview on Science and Technology Research Vol. 6, 2022)
Attendance marking during a lecture in a classroom is not only challenging but also a time-consuming task. There will always be a possibility of proxy attendance. It's proven to be difficult to track attendance using traditional ways. In recent years, common biometrics like fingerprints are used to overcome the problem of automatic attendance marking. Rather than using traditional methods, the suggested solution intends to create an automated system that uses facial recognition technology to record the student's attendance. The primary goal of this project is to make the attendance tracking and management system more efficient, time-saving, simple, and straight-forward. Face recognition techniques will be used here to identify faces. The processed image will then be compared to the existing stored record and attendance will be recorded accordingly in the database.